KEPERCAYAAN MASYARAKAT TERHADAP TEMPAT KERAMAT DI DESA SILAU MARAJA KECAMATAN SETIA JANJI KABUPATEN ASAHAN - Lubis, Kholila Rahma; Ritonga, Sakti; Ismail, Ismail (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
Indonesian people still believe in places that they consider to have supernatural powers. In certain communities, such as the village of Silau Maraja, there are certain places and spaces that are considered by the community to have a special position, which is called the community of sacred places. The Silau Maraja community has carried out various ways to protect the sacred place where there is an irrigation dam in the belief that it will provide safety and peace to the community, which is called the "Nature of Bali" community. In this thesis, the purpose of this research is to look at the factors that society maintains belief in the place "Bali's nature as a sacred place. And to see the social function of this sacred place in the Silau Maraja community. In this study using a qualitative approach method. In this case, to obtain the intended data, the selection of research subjects in the Silau Maraja community was seven people, such as religious leaders, agricultural communities, community leaders and guardians of the Bali natural dam. Data collection techniques researchers conducted observations and interviews with informants and documentation. From the results of this study it was found that the community's belief system for sacred places is still maintained and becomes a source of livelihood for the community because they are a source of water for rice fields. The researcher uses Talcot Parsons Functionalism theory which says society is seen as an interconnected system and there is not a single part that does not have a function. Likewise in research related to functionalism theory that people's belief in sacred places has a relationship with each other that is interrelated and has a social function arising from sacred places to protect nature and protect the environment.